Population Dynamics, Breeding Success, and Conservation Implications of Crocodylus palustris in Captive and Semi-Natural Systems across India: Dinámica poblacional, éxito reproductivo e implicaciones para la conservación de Crocodylus palustris en sistemas cautivos y seminaturales en la India (Veterinary Science, 2026)
The mugger crocodile (Crocodylus palustris), classified as Vulnerable by the IUCN and protected under Schedule I of the Wildlife (Protection) Act, 1972, functions as a keystone wetland predator across the Indian subcontinent. A comprehensive analysis of 2024 Central Zoo Authority (CZA) records from 45 facilities across 12 Indian states (n = 1,187 individuals) revealed an average annual captive population growth of 18.5%, driven primarily by inter-facility transfers rather than natality (78% transfer contribution). Overall mortality was 2.53%, with juveniles (
Keywords: Crocodylus palustris; captive breeding; Temperature-dependent sex determination; Juvenile mortality